(untitled) (The Science Post, 2025)
In The rapid expansion of telehealth services, accelerated by the COVID-19 pandemic, presents significant challenges for healthcare organizations in managing complex implementation projects. Effective project management tools tailored specifically for telehealth are lacking, resulting in coordination inefficiencies and increased risk of regulatory non-compliance. This study proposes the development of a specialized project management dashboard designed to streamline telehealth implementation by integrating real-time task tracking, regulatory monitoring, resource allocation, and stakeholder communication into a unified platform. Using a mixed-methods approach, including stakeholder surveys, system performance testing, and user feedback analysis, the dashboard was iteratively refined to meet diverse user needs across clinical, administrative, and technical roles. Results demonstrate improved project visibility, enhanced collaboration, and increased adherence to compliance requirements. Key performance metrics indicate that the dashboard achieves high usability and system responsiveness, supporting agile project workflows. The study concludes with recommendations for further integration of predictive analytics and enhanced user training to maximize adoption. This research contributes a practical tool and a framework for managing telehealth projects more effectively, with implications for healthcare providers, IT teams, and policymakers aiming to expand digital health services.